Access to Water and the SARs-Cov-2 Pandemic: Opportunities and Threats in a Post-Pandemic Era for sub-Saharan Africa - Williams Kwari Joshua (Program Pascasarjana Universitas Sriwijaya, 2022)
The emergence of SARs-Cov-2 has severely impacted on the progress made so far on the sustainable development goals in SSA. The current ineffective water and healthcare sectors in many African countries could serve as a deterrent to an impending crisis. This mini review aims to highlight the opportunities and threats to the water and healthcare sector in a post pandemic era. Recent studies indicate that the virus have been found in water bodies including wastewater and sewage and this could serve as a potential medium of mutation of the virus. In addition, SSA have poor waste management implementation and sanitation especially within rural and densely populated areas. This coupled with lack of adequate supply of potable water can see SSA fall back in achieving the SDGs. The struggle against climate change and recently Covid-19 will devastate socio-economic development of many countries within the SSA region. Climate change has impacted on water accessibility and quality and Covid-19 requires adequate water supply to reduce human-to-human transmission. This will see a severe stress on already existing stresses in the water and health sectors which can eventually led to a system collapse. Urgent attention is therefore required through the design and implementation of programs aimed at building resilience to climate impacts and prepare for future pandemics.